International Effects of Euro Area Forward Guidance - Böck, Maximilian; Feldkircher, Martin; Siklos, Pierre L (Oxford Bulletin of Economics and Statistics, 2021)
In this paper, we investigate the international effects of euro rate forward guidance (FG) and compare them to spillovers from a conventional monetary policy shock (MP). We identify the forward guidance shock via a combination of zero and sign restrictions that use the relationship between expectations and observed data and additionally draw on insights from recent event studies using high-frequency data. To address potential time variation, we use a fully flexible approach that allows to handle both drifts in residual variances and the structural coefficients. Our results show that both shocks lead to considerable international effects on output growth, inflation and equity returns. Moreover, we find that effects are stronger during the period of the global financial crisis, which is particularly true for the FG shock. This implies that monetary policy is generally not hindered in affecting the real economy by the zero lower bound. Also, shocks to expectations can have real domestic effects with international consequence